2020
DOI: 10.1002/ajim.23100
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the accuracy of the death certificate injury at work box for identifying fatal occupational injuries in Michigan

Abstract: BackgroundDeath certificates contain a box labeled “Injury at Work” which is to be marked “Yes” for all fatal occupational injuries. The accuracy of this box in Michigan is not fully characterized.MethodsThe accuracy of the Injury at Work box on the Michigan death certificate was compared to deaths identified from 2001 through 2016 by the Michigan Fatality Assessment and Control Evaluation multi‐source surveillance system. The sensitivity was calculated across this time period, while specificity and positive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…For example, for this study period of 2013–2017, the death certificate identified 1.13% of suicides as work‐related, but when all three sources were considered, the proportion was 12.11%. Prior studies found that under‐reporting of occupational injury occurred by sex, age, and mechanism of injury 4–6 . These studies have found that work‐relatedness is undercounted in death certification overall and that this undercount is disproportional for suicides.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…For example, for this study period of 2013–2017, the death certificate identified 1.13% of suicides as work‐related, but when all three sources were considered, the proportion was 12.11%. Prior studies found that under‐reporting of occupational injury occurred by sex, age, and mechanism of injury 4–6 . These studies have found that work‐relatedness is undercounted in death certification overall and that this undercount is disproportional for suicides.…”
Section: Discussionmentioning
confidence: 98%
“…A study in Michigan estimated the sensitivity from 2001 through 2016 to be 73.1% overall, although for suicides was only 61.9%. Sensitivity decreased over time and reached 63.1% in 2016 6 . In a survey of California Medical Examiners, only 38.9% reported that they would consider a suicide as work‐related even if it occurred during paid work and in the decedent's workplace 5 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, all traumatic work‐related cases should theoretically be captured by the surveillance system without limitations such as industry, business size, or type of employment (i.e., public, private, or self‐employed). While the true sensitivity of the CFOI system may be unknown, a study comparing the death certificate's Injury‐At‐Work item to a multi‐source surveillance system showed that both the manufacturing industry and machinery‐related incidents had high levels of sensitivity, suggesting a greater likelihood of robot‐related incidents being captured by CFOI 35 …”
Section: Discussionmentioning
confidence: 99%
“…The Census of Fatal Occupational Injuries, which relies on the death certificate, worker’s compensation records, and newspaper reports, estimates that 1% to 3% of suicides are work-related. Although the Census of Fatal Occupational Injuries has been the most comprehensive data to identify occupational fatalities, its sources have limited information on suicide circumstances and thus estimates for suicide are considerably low [ 9 , 10 , 11 ]. Data from the National Violent Death Reporting System, which includes more in-depth investigation of circumstances associated with suicide and homicide, identified work factors in 13.5% of suicides [ 12 ].…”
Section: Introductionmentioning
confidence: 99%